2019
DOI: 10.1039/c9ra08336g
|View full text |Cite
|
Sign up to set email alerts
|

Human periodontal ligament stem cells on calcium phosphate scaffold delivering platelet lysate to enhance bone regeneration

Abstract: Human periodontal ligament stem cells (hPDLSCs) are promising for tissue engineering applications but have received relatively little attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…The relatively lower expression in nanofiltered growth media could possibly be linked in part to a decrease of FGF content because this growth factor plays a key role in osteogenesis by activating RUNX2, which regulates bone formation and growth, and participates in the anabolic function of osteoblasts [61,62]. Gene expression data obtained here are consistent with previous reports on the stronger stimulation of chondrogenic and osteogenic differentiation using human platelet lysates than FBS [22,30,63].…”
Section: Discussionsupporting
confidence: 89%
“…The relatively lower expression in nanofiltered growth media could possibly be linked in part to a decrease of FGF content because this growth factor plays a key role in osteogenesis by activating RUNX2, which regulates bone formation and growth, and participates in the anabolic function of osteoblasts [61,62]. Gene expression data obtained here are consistent with previous reports on the stronger stimulation of chondrogenic and osteogenic differentiation using human platelet lysates than FBS [22,30,63].…”
Section: Discussionsupporting
confidence: 89%
“…Metformin (a small molecular glucose lowering drug) and platelet lysate (HPL) carried by CPC-chitosan scaffold can be sustainably released for 15-21 days (Qin et al, 2018;Qiu et al, 2021). Metformin and HPL released by CPC increased the osteogenesis of PDLSCs seeded on CPC scaffolds (Qin et al, 2018;Zhao et al, 2019c).…”
Section: Delivery Of Pdlscs With Various Types Of Scaffoldsmentioning
confidence: 98%
“…Chitosan can be used as a viscous binder to rendered CPC fast-setting and increase the load-bearing capability (Wang et al, 2016). CPC scaffold containing chitosan is an effective delivery vehicle for drugs and proteins (Zhao et al, 2019b;Zhao et al, 2019c). Qin et al (2018) and Qiu et al (2021) revealed that CPC-chitosan scaffolds can sustainably release small molecular drug and growth factors.…”
Section: Delivery Of Pdlscs With Various Types Of Scaffoldsmentioning
confidence: 99%
“…Besides the development of 3D hierarchical scaffolds, the use of biologicals is currently under investigation to enhance the scaffold performance without scar formation. Recently, various biologics combined with scaffolds have been considered and evaluated in preclinical animal studies to augment tendon repair [ 114 , 115 , 116 ]. The main goal is to achieve a complete functional recovery of the tendon injuries [ 10 , 117 ].…”
Section: Biological Augmentation For Tendon Healingmentioning
confidence: 99%